Les espaces économiques industriels spécialisés : les patrons de mobilité des travailleurs et l’accessibilité en transport en commun - Sylvie Arbour; Élisabeth B. Monrency (VertigO, 2012)
Transportation is an intermediate consumption service. It is therefore an auxiliary of the professional activities of individuals, their leisure and the production system in which they evolve. In this context, it is important to understand the determinants of people’s mobility in order to derive their transportation needs. This paper focuses more specifically on these determinants. The objective is twofold : to study the patterns of the daily trips of workers to specialized industrial spaces in the metropolitan area of Montreal and to analyze the accessibility to these spaces by means of public transportation. The research is based on the data from the 2003 origin-destination survey in the region and the offer of transit system networks.